Network‐based recruitment of people who inject drugs for hepatitis C testing and linkage to care. Issue 7 (2nd March 2020) - Falade‐Nwulia, Oluwaseun; Ward, Kathleen M.; McCormick, Sean; Mehta, Shruti H.; Pitts, Stephanie R.; Katz, Stephanie; Chander, Geetanjali; Thomas, David L.; Sulkowski, Mark; Latkin, Carl A.
Abstract: Although oral direct‐acting agent (DAA) therapies have the potential to reduce the burden of hepatitis C virus (HCV) infection, treatment uptake remains low, particularly among people who inject drugs (PWID). This study examined the feasibility of an innovative peer‐based recruitment strategy to engage PWID in HCV testing and treatment. We interviewed an initial set of HCV antibody‐positive PWID as 'primary indexes' to gather demographic, drug use, health information and drug network characteristics. Primary indexes were then briefly educated on HCV and its treatment and encouraged to recruit their injection drug 'network members' for HCV testing and linkage to care. Eligible network members were enrolled as 'secondary indexes' and completed the same index study procedures. In sum, 17 of 36 primary indexes initiated the recruitment of 64 network members who were HCV antibody positive and eligible to become indexes. In multivariable analysis, successful recruitment of at least one network member was positively associated with prior HCV treatment (OR 2.80; CI [1.01, 7.72]), daily or more injection drug use (OR 2.38; CI [1.04, 5.47]), and a higher number of injection drug network members (OR 1.20; CI [1.01, 1.42]). Among the 69 participants with chronic HCV not previously linked to HCV care at enrolment, 91% (n = 63) completed a linkage to HCV care appointment, 45% (n = 31) scheduled an appointment with an HCV provider, and 20% (n = 14) initiated HCV therapy. These findings suggest a potential benefit for peer‐driven, network‐based interventions focused on HCV treatment‐experienced PWID as a mechanism to increase HCV linkage to care.